Spin polarization and magneto-luminescence of confined electron-hole systems (2001)
ABSTRACT: A BCS-like variational wave-function, which is exact in the infinite field limit, is used to study the interplay among Zeeman energies, lateral confinement and particle correlations induced by the Coulomb interactions in strongly pumped neutral quantum dots. Band mixing effects are partially incorporated by means of field-dependent masses and g factors. The spin polarization and the magneto-luminescence are computed as functions of the number of electron-hole pairs present in the dot and the applied magnetic field.